The Evaluation of Receivables and Inventories as an Integral Part of Credit Analysis (Book). - Miller, Herbert E.; Flatley, L. Thomas (The Accounting Review, 1945)
Abstract Reviews the book "The Evaluation of Receivables and Inventories As an Integral Part of Credit Analysis," by Edward F. Gee.